The Study Of Customer Satisfaction in Murah Rezeki Motorcycle Workshop Stabat, Sumatera Utara - Sarmauli Hanny Siagian; Nasrul Effendy; M. Umar Maya Putra; Kevin Huang (Journal of Research in Business, Economics, and Education, 2022)
The development of the automotive industry has not been matched by the existence of workshops for motorcycles. In some areas, the number of workshops cannot cover the needs their need as to. the customer satisfaction so that in this study is needed to indicate the variable observed such as service quality, price, and location in Murah Rezeki Motorcycle Workshop Stabat, either simultaneously or partially. The type of research used in this research is descriptive research with a quantitative approach. The sampling technique used incidental sampling method with a total sample of 96 respondents. The data analysis method is the multiple linear regression analysis. The result found that the variables of service quality, price, and location partially and simultaneously affect customer satisfaction. The result of the coefficient of determination is 35%. It shows that the variables consisting of service quality, price, and location affect the customer satisfaction variable by 35.0%, while the remaining 65% is explained by other variables not examined in this study.